Age-Specific Prevalence of Visual Impairment and Refractive Error in Children Aged 3–10 Years in Shanghai, China - Ma, Yingyan; Qu, Xiaomei; Zhu, Xiaofeng; Xu, Xun; Zhu, Jianfeng; Sankaridurg, Padmaja; Lin, Senlin; Lu, Lina; Zhao, Rong; Wang, Ling; Shi, Huijing; Tan, Hui; et al. (Investigative ophthalmology & visual science, 2016)
We assessed changes in age-specific prevalence of refractive error at the time of starting school, by comparing preschool and school age cohorts in Shanghai, China. A cross-sectional study was done in Jiading District, Shanghai during November and December 2013. We randomly selected 7 kindergartens and 7 primary schools, with probability proportionate to size. Chinese children (n = 8398) aged 3 to 10 years were enumerated, and 8267 (98.4%) were included. Children underwent distance visual acuity assessment and refraction measurement by cycloplegic autorefraction and subjective refraction. The prevalence of uncorrected visual acuity (UCVA), presenting visual acuity, and best-corrected visual acuity in the better eye of ≤20/40 was 19.8%, 15.5%, and 1.7%, respectively. Among those with UCVA ≤ 20/40, 93.2% could achieve visual acuity of ≥20/32 with refraction. Only 28.7% (n = 465) of children with UCVA in the better eye of ≤20/40 wore glasses. Prevalence of myopia (spherical equivalent ≤-0.5 diopters [D] in at least one eye) increased from 1.78% in 3-year-olds to 52.2% in 10-year-olds, while prevalence of hyperopia (spherical equivalent ≥+2.0 D) decreased from 17.8% among 3-year-olds to 2.6% by 10 years of age. After adjusting for age, attending elite "high-level" school was statistically associated with greater myopia prevalence. The prevalence of myopia was lower or comparable to that reported in other populations from age 3 to 5 years, but increased dramatically after 6 years, consistent with a strong environmental role of schooling on myopia development.